Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1371/journal.pone.0189377
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the diagnosis of ulcerative colitis with concomitant bacterial infections and chronic infectious colitis

Abstract: Ulcerative colitis (UC) is a chronic inflammation of the large bowel characterized by diarrhea and a negative stool culture. However, several enteropathogens have been implicated as causative agents in UC. The differentiation between chronic infectious colitis (IC) and UC with concurrent infection is difficult owing to their similar clinical presentations. The study aimed to explore the presentations and diagnostic clues that enable differentiation between UC with concomitant infections and chronic IC. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 24 publications
0
7
1
Order By: Relevance
“… 49 However, there are many efforts to improve awareness about IBD and to improve access to medical services to differentiate acute infectious colitis from IBD. 52 Nevertheless, more than 300000 Indians are estimated to have CD, and 1.1 million people have UC in India. Because of the large population of India, with more than 120 million, the total IBD burden of India could be highest in the world.…”
Section: Epidemiology Of Ibd In Indigenous Asiansmentioning
confidence: 99%
“… 49 However, there are many efforts to improve awareness about IBD and to improve access to medical services to differentiate acute infectious colitis from IBD. 52 Nevertheless, more than 300000 Indians are estimated to have CD, and 1.1 million people have UC in India. Because of the large population of India, with more than 120 million, the total IBD burden of India could be highest in the world.…”
Section: Epidemiology Of Ibd In Indigenous Asiansmentioning
confidence: 99%
“…Chronic diarrhea sometimes can be a very challenging clinical scenario due to multitude of differential diagnoses to consider. The majority of the macroscopic findings during endoscopic evaluation are unremarkable or nonspecific [9]. Greenson et al in their study on adult population reported that endoscopic findings of FAC varied.…”
Section: Discussionmentioning
confidence: 98%
“…A recent retrospective study by Lin et al . sought to identify features that could be used to differentiate these two clinical entities . Young age, bloody diarrhoea, poor antibiotic response and cryptitis together with crypt abscesses on histology were found to be significant .…”
Section: Discussionmentioning
confidence: 99%
“…sought to identify features that could be used to differentiate these two clinical entities . Young age, bloody diarrhoea, poor antibiotic response and cryptitis together with crypt abscesses on histology were found to be significant . Considerable overlap has been noted between the clinical, endoscopic and histological features of infectious colitis and UC.…”
Section: Discussionmentioning
confidence: 99%